PERANAN LEMBAGA NAGARI DALAM MENINGKATKAN PEMBANGUNAN DI NAGARI AIA AMO KABUPATEN SIJUNJUNG - Ade Hendra; Maiyulnita Maiyulnita; Nasrizal Nasrizal (Jurnal Public Administration, Business and Rural Develoment Planning, 2021)
The purposes of this research are to determine the Role and the development program of theNagari Aia Amo Institution, Kamang Baru District, Sijunjung Regency. The resulf of thisreaserch showed that the role of the Nagari Institution as a community coach in serving theNagari government community can be said to have satisfied residents so that the developmentcarried out in Aie Amo Data can run or carried out smoothly because of the support from theentire community. The services provided by the Nagari government to the community in thiscase are in the form of processing documents for which there is no standard fee. 2) Thedevelopment program in Nagari Aie Amo can be seen from the intensive efforts of guardingthe Nagari government apparatus including the Nagari Wali and their staff who collaboratewith the Head of Jorong who is a community leader in the area. As a lower level governmentthe Nagari government can only propose and assist all physical developments determined bythe MUSREMBANG results at the sub-district level. Because the Nagari government can onlycarry out coordination orders from the sub-district level government which is itsadministrative area 3) The role of Nagari institutions in Nagari Aia Amo Development,Kamang Baru Subdistrict, Sijunjung Regency This fairly good community participation isevident from the various attention from the community towards all developments in thescope of government of Nagari Aie Amo 2). Cooperation between fellow Devices is veryharmonious between fellow Nagari Devices, in the form of intimacy that occurs betweenfellow Devices, as well as the obedience of all Devices to the Wali Nagari Mother.